Frequency, Prevalence, and Burden of Flares on Patients with Moderate to Severe Psoriasis: A Retrospective Cross-Sectional Analysis. Issue 3 (June 2017) - Hsu, Ming-Ann; Lucas, James; Wood, Robert; Cappelleri, Joseph C.; Piercy, James
Background: Psoriasis impairs health-related quality of life (HRQoL). Objective: To improve understanding of flare burden in patients with moderate to severe psoriasis. Methods: A retrospective, cross-sectional study comparing data in U.S. patients with and without psoriasis flares. Physicians identified flaring patients as those not in remission, or in remission < 12 weeks, with worsening/unstable disease progression. Results: Overall health status (EQ-5D-3L) was reduced in flaring versus matched non-flaring patients ( P = .001); this difference was clinically meaningful (> 0.074 difference in absolute value). Reduced HRQoL and activity impairment, measured by Dermatology Life Quality Index ( P = .0178) and Work Productivity and Activity Impairment Questionnaire ( P = .0002), respectively, were observed in flaring versus non-flaring patients. Anxiety was associated with flaring ( P = .0139). Flaring patients were less satisfied with treatment effectiveness than non-flaring patients ( P < .0001). The flaring group experienced a median of two flares over 12 months. Conclusion: Flares are associated with reduced health status and HRQoL and lower treatment satisfaction.